2015
DOI: 10.1140/epje/i2015-15103-7
|View full text |Cite
|
Sign up to set email alerts
|

On the phase transitions of 8CB/Sn2P2S6 liquid crystal nanocolloids

Abstract: Using differential scanning calorimetry measurements, the influence of Sn2P2S6 ferroelectric nanoparticles on the phase transition temperatures of the 8CB liquid crystal is studied. The spontaneous polarization, ionic and anchoring effects are discussed. For low concentration of dopant, the global effect leads to a decrease and an increase of the nematic-isotropic and the smectic A-nematic phase transition temperatures, respectively. For high concentrations, due to aggregates formation, the predominant anchori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…The nanoparticles were prepared by milling microsized particles together with oleic acid in a vibration mill for 120 h. The oleic acid was used as a surfactant on the nanoparticles' surfaces in order to avoid the formation of aggregates. 8 The nanoparticle suspension was obtained at a concentration of 0.1 wt%. The morphology of the resulting particles was characterized using atomic force microscopy (AFM, Veeco multimode equipped with a nanoscope IIIa controller, power of diode laser: 1 mW, l ¼ 690 nm) by depositing the nanoparticle/heptane stabilized suspension on quartz substrate by a dip coating method, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The nanoparticles were prepared by milling microsized particles together with oleic acid in a vibration mill for 120 h. The oleic acid was used as a surfactant on the nanoparticles' surfaces in order to avoid the formation of aggregates. 8 The nanoparticle suspension was obtained at a concentration of 0.1 wt%. The morphology of the resulting particles was characterized using atomic force microscopy (AFM, Veeco multimode equipped with a nanoscope IIIa controller, power of diode laser: 1 mW, l ¼ 690 nm) by depositing the nanoparticle/heptane stabilized suspension on quartz substrate by a dip coating method, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For the non-harvested nanoparticles dispersed with the 8CB liquid crystal, we previously showed that the volume concentration, f NP ¼ 0.08%, allows optimization of the effects of the nanoparticles. 8,13 Moreover this concentration corresponds to a homogeneous dispersion. For these reasons, this concentration was chosen for nanocolloid #2.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations